Automation in Waste Management: How AI and Robotics Transforming Waste Sorting and Recycling - J. V. Pesha; L. M. R. Rangesh; B. Praadap; V. Abhishek; A. Vishnuvardhan (International Journal of Advanced Control and System Engineering, 2025)
Waste management is a big issue in the modern world, and it gets worse as urbanisation and industry increase. Hazards to the environment and human health result from traditional waste management practices' inability to effectively classify, recycle, and dispose of garbage. Robotics and artificial intelligence (AI) provide creative ways to improve trash processing, sorting, and collection. This article examines the application of robotics and artificial intelligence (AI) to waste management, emphasising the methods, importance, and possible advantages of each. Robotics, such as autonomous and robotic sorting systems, enable faster, safer, and more accurate handling of waste materials, while AI-driven algorithms improve route optimization, predictive analytics, and recycling accuracy. By increasing recycling rates and decreasing the need for landfilling, these technologies lower operating costs and minimise environmental effects. Additionally, AI’s ability to predict waste generation patterns and optimize resource allocation supports more sustainable waste management practices. But issues including high upfront costs, workforce relocation, and technological adaptation need to be addressed. This paper explores the potential of AI and robotics to revolutionize the waste management industry, presenting a forward-looking perspective on how these technologies can drive efficiency, sustainability, and cost-effectiveness in managing solid waste.
Keywords: Adaptation; Artificial Intelligence (AI); Environmental sustainability; Landfilling; Robotics and Automation (RA); Solid Waste Management; recycling